Magnetic resonance imaging findings of intravascular leiomyomatosis of the uterus: a case report - Guo, Bin; Zhao, Shuhui; Li, Juan; Wang, Xiaoyan (Frontiers in Medicine, 2024)
Background Intravascular leiomyomatosis (IVL) is often a non-malignant condition that grows inside the blood vessels and does not invade surrounding tissues. However, its presence within the blood vessels can lead to obstructions. The majority of IVL cases manifest symptoms related to blockage. Case presentation We present a case of a 50-year-old female patient who was referred to our institution due to the presence of a common non-cancerous tumor in the uterus, known as a benign uterine leiomyoma. The tumor was identified during an ultrasound examination during a routine physical examination. Postoperative pathology established the existence of intrapelvic IVL. Conclusion Intrapelvic IVL often not present with complications when it is confined to the pelvic cavity. Furthermore, the imaging features of intrapelvic IVL resemble those of typical benign uterine leiomyomas. This can often result in the clinical misdiagnosis of the tumor as a typical benign uterine leiomyoma.